Implementing new technologies in maintenance systems and departments in Europe. (Research results digest (Transit Cooperative Research Program), 2005)
"This TCRP digest summarizes the mission performed April 7-22, 2005, under TCRP Project J-3, "International Transit Studies Program." This digest includes transportation information on the cities and facilities visited. This digest was perpared by the staff of the Eno Transportation Foundation and is based on reports filed by the mission participants." -- p. 1.